VERSATILE MEASURING DEVICE FOR THE STUDY OF MAGNETIC PROPERTIES OF SOLIDS - COSMA, Ioan (Studia Universitatis Babeș-Bolyai Physica, 2017)
As a zero apparatus, our measurement device is based on the Faraday method. We have made two compensation systems; mechanical and electromagnetic. It is adapted to the translational movements for insertion of the sample between the poles of the electromagnet that creates a field with an appropriate gradient of operation. To the balance can attach either a non-inductive furnace that provides sample heating up to 1900 K, or a cryostat that provides a controlled cooling temperature and a return temperature between ambient and to liquid nitrogen temperature. Susceptibility and magnetization are assessed in a relative mode; calibration using standard samples of high trust. Magnetic properties studies, versus temperature and intensity the magnetic field, on hundreds materials of thousand different metallic, vitreous and crystalline and oxidic superconductor samples, have been confirmed with similar research, demonstrating the versatility and utility of our measuring system for many years.